How to think more about sex - De Botton, Alain, 1969- (London : Macmillan, 2012)
In this rigorous and supremely honest book Alain de Botton helps us navigate the intimate and exciting – yet often confusing and difficult – experience that is sex. Few of us tend to feel we're entirely normal when it comes to sex, and what we're supposed to be feeling rarely matches up with the reality. This book argues that 21st-century sex is ultimately fated to be a balancing act between love and desire, and adventure and commitment. Covering topics that include lust, fetishism, adultery and pornography, Alain de Botton frankly articulates the dilemmas of modern sexuality, offering insights and consolation to help us think more deeply and wisely about the sex we are, or aren't, having.
Keywords: Seksualiteit